Repeated assessments of physical activity and risk of incident venous thromboembolism - Evensen, Line Holtet; Isaksen, Trond; Hindberg, Kristian; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (Journal of Thrombosis and Haemostasis, 2018)
This is the peer reviewed version of the following article: Evensen, L., Isaksen, T., Hindberg, K., Brækkan, S.K. & Hansen, J.-B. (2018). Repeated assessments of physical activity and risk of incident venous thromboembolism. Journal of Thrombosis and Haemostasis, 16 (11), 2208-2217, which has been published in final form at https://doi.org/10.1111/jth.14287 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Background : Whether physical activity influences the risk of incident venous thromboembolism (VTE) remains controversial, potentially because of methodological challenges, such as regression dilution bias. Objectives : To investigate whether physical activity was associated with VTE risk, and explore the role of body mass index (BMI) as a mediator in a population‐based cohort with repeated assessments of physical activity. Methods : Participants (n = 30 002) attending one or more surveys of the Tromsø Study 4–6 (1994–1995, 2001–2002, and 2007–2008) were included and categorized on the basis of weekly physical activity. Incident VTE was registered until 31 December 2016. Hazard ratios (HRs) were calculated by the use of time‐varying Cox regression models. The Aalen additive hazard model was used to quantify the total, direct and indirect effects of physical activity. Results : There were 531 incident VTEs during follow‐up. Physical activity (≥ 1 per week) was associated with a lower risk of VTE (HR 0.77, 95% confidence interval [CI] 0.64–0.92) than being inactive. The effect was most pronounced for those aged ≥ 65 years (HR 0.70, 95% CI 0.55–0.88) and for provoked events (HR 0.66, 95% CI 0.50–0.89). The differences in absolute risk between active and inactive individuals were − 0.42 (95% CI − 0.73 to − 0.14) and − 1.59 (95% CI − 2.74 to − 0.52) events annually per 1000 individuals in the total and elderly populations, respectively. A moderate proportion of the association (14–36%) was mediated via BMI. Conclusion : Our ...